The effect of A23187 ionophore on calcium movements and contraction processes in single barnacle muscle fibres. - Desmedt, J E (1976)
1. Ca movements were studied in single giant muscle fibres of the barnacle before and after exposure to the Ca ionophore A23187. 2. In fibres micro-injected with the photoprotein aequorin, the resting rate of light emission (resting glow) reversibly increased when the external Ca was augmented in the presence of A23187. This resulted from an increased Ca influx through the outer membrane. In zero external Ca, A23187 induced a delayed increase of the resting glow which was related to Ca leakage from intracellular storage sites. 3. When the experiment was carried out at 5 degrees C instead of 22 degrees C, the resting glow about doubled (temperature-sensitive mechanisms for maintaining a low myoplasmic Ca2+ were thus depressed) but A23187 was much less effective in increasing Ca influx in high external Ca. 4. In 45Ca efflux experiments, A23187 increased both the Ca-Ca exchange diffusion and the net Ca outflux at the outer membrane of the fibre. The Na-Ca exchange process was not affected to a significant extent. 5. The Ca2+ transient and the force of the contraction elicited by imposed membrane depolarizations (below the threshold of the propagated action potential) were markedly increased by A23187, but the electromechanical threshold was not significantly modified. The linear relation between membrane depolarizations and the area of the Ca transient became much steeper in the presence of A23187. However the relation between the area of the Ca transient and the force output was not affected which suggests that A23187 specifically involved the Ca2+ intracellular release, but not the subsequent Ca-troponin reaction. 6. A23187 potentiates by ionophoretic action the Ca movements at the outer membrane, and it also acts inside the intact muscle fibre to intensify the intracellular release of Ca.